Changes in biomechanical parameters during heart perfusion and after midazolam pre-medication - experimental pilot study - Bartošíková, Lenka; Nečas, Jiří; Bartošík, Tomáš; Fráňa, Petr; Pavlík, Martin (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2008)
Background: Midazolam is a frequently used benzodiazepine in anaesthesiology and intensive care.Aim: The aim of pilot study was to monitor its eff ect during heart perfusion in the laboratory rat.Methods: The same groups of animals (n = 10). The 1st group was treated with midazolam in a dose of 0.5mg/kgi.p. The 2nd group was a placebo. After i.p. administration of heparine injection of 500 IU dose, the hearts were excisedand perfused (modifi ed Langendorf’s method). Working schedule: stabilization/ischaemia/reperfusion proceed at intervalsof 20/30/60 min. Monitored parameters in isolated heart: left ventricle pressure (LVP), end-diastolic pressure(LVEDP), contractility (+dP/dtmax).Results: The treated hearts showed improved postischemic recovery, reaching LVP values of 92 ± 6 % at the end ofthe reperfusion, placebo only 61 ± 7 %. In placebo hearts LVEDP rose from 10.0 ± 0.5 mmHg to 43 ± 4 mmHg after,in treated animals only about 25 mmHg. The treated hearts improved +dP/dtmax recovery during reperfusion to 91 ±8 %. These values were signifi cantly greater than those obtained from the placebo hearts.Conclusions: Positive changes in monitored parameters were found in this experimental pilot study. We concludethat the administration of midazolam in laboratory rats has a cardioprotective potential against ischemia-reperfusioninduced injury.
Keywords: experimenty na zvířatech; statistika jako téma; Animals; Myocardial Reperfusion; Rats, Wistar; Evidence-Based Medicine; reperfuze myokardu; Statistics as Topic; kardiotonika; midazolam; Animal Experimentation; medicína založená na důkazech; ischemická choroba srdeční; Midazolam; měření krevního tlaku; Pilot Projects; Blood Pressure Determination; zvířata; pilotní projekty; Cardiotonic Agents; Myocardial Ischemia; potkani Wistar